The Role of Emotional Intelligence in the Performance of an Organisation with 2 Mediating Variables: a Case Study Approach - Tee Suan .Chin, Susan; Dr. Rosman, Prof (International Journal of Engineering and Technology, 2018)
As organisations enter the 21st century, the dynamism of the business environment has certainly increased its pace. The external environment especially the technological element has accelerated the changes in the business platform. Many organisations who are unable to keep up with these changes has to wrap up. Those in the business needs to look for a strong strategic asset which can be used not only for sustainability but to propel the business into higher realms. In the 1980s-1990s, a few studies have highlighted the usage of emotional intelligence as a source of performance among their employees. The purpose of this study is to study the role of emotional intelligence in the performance of an organisation with 2 mediating variables. A case study approach has been used in this study. It was found that with the mediating variables in play, the role of emotional intelligence has certainly enhanced.Â Â